Analysing terrorist networks – An entropy‐driven method. Issue 10 (25th May 2021) - Rödder, Wilhelm; Dellnitz, Andreas; Litzinger, Sebastian
Abstract: Terrorism is a scourge of humanity. Thousands of people were killed by terrorists in the last years. To understand the structure, information flow and leadership in terrorist cells is a must for all societies to prevent future attacks. Network theory can help to model such cells and to identify leading members therein. This contribution uses the graph theoretical approach as a basis and enriches it by an entropy‐driven knowledge processing. After presenting the theoretical concept two terrorist cells, the one of the Bali attack and the one of the 9/11 attack, are analysed. The results are compared to those of other methods. A preview on the application of weighted networks and multi‐nets complements the new findings.